DINAMIKA TOLERANSI BERAGAMA MENJELANG PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN 2024ANALISIS ISI TERHADAP BERITA POLITIK( STUDI PADA PORTAL MEDIA BERITA ONLINE KOMPAS.COM ) - Aulia, Reza aulia; Aulia, Reza; Akhyar, Taufik; Fadli, Najmi Muhammad (Jurnal Studi Ilmu Politik, 2024)
This research is motivated by the phenomenon before the presidential election that the use of religious symbols is prone to occur anywhere and at any time, including in the news, one of the media that covers religious tolerance during the presidential and vice presidential elections is the news media kompas.com. This research aims to determine the dynamics of religious tolerance in the lead up to the 2024 presidential and vice presidential elections on the media portal kompas.com. This research method uses a qualitative approach and is included in the type of library research, primary research data comes from the online media kompas.com, and secondary data. The data collection techniques used are document review or what is usually called documentation, and data analysis techniques, data reduction, data analysis and drawing conclusions. The results obtained were Kompas.com’s reporting regarding religious tolerance ahead of the 2024 presidential election with aspects according to Kevin Osborn, namely that acceptance in political news was used as recognition from other people. Tolerance in the aspect of patience is a form of availability for other people to be patient with other people’s beliefs, morals and philosophies even though they are different. Kompas.com’s framing of political news using Robert N. Entman’s framing theory in this news has described the state of religious tolerance in several regions. Apart from that, the discussion regarding religious tolerance involved several other important figures.Keywords: Religious Tolerance, 2024 Presidential Election, Kompas.com